Relasi Antara Doa dan Ketenangan Jiwa dalam Perpekstif Psikologi Agama - Muhammad Jalaludin Rumi Hamid; Ahmad Syihabuddin Albuny; Salman Alfarizi; Yuminah Yuminah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study explores the relationship between prayer and inner peace from the perspective of religious psychology. Prayer is not only seen as a ritualistic act of worship but also as a spiritual coping mechanism that positively impacts psychological well-being. This research employs a literature review method by analyzing various relevant sources. The findings indicate that prayer plays a significant role in reducing stress, strengthening inner resilience, and fostering a sense of peace. A positive correlation is found between prayer frequency and the level of inner calmness, particularly among university students and the elderly. The study suggests that prayer can be utilized as a spiritual approach to support mental health, especially amid the challenges of modern life.